Extracellular Vesicle-Mediated Network in the Pathogenesis of Obesity, Diabetes, Steatotic Liver Disease, and Cardiovascular Disease - Lee, Joonyub; Choi, Won Gun; Rhee, Marie; Lee, Seung-Hwan (Diabetes & metabolism journal, 2025)
Extracellular vesicles (EVs) are lipid bilayer-enclosed particles carrying bioactive cargo, including nucleic acids, proteins, and lipids, facilitating intercellular and interorgan communication. In addition to traditional mediators such as hormones, metabolites, and cytokines, increasing evidence suggests that EVs are key modulators in various physiological and pathological processes, particularly influencing metabolic homeostasis and contributing to the progression of cardiometabolic diseases. This review provides an overview of the most recent insights into EV-mediated mechanisms involved in the pathogenesis of obesity, insulin resistance, diabetes mellitus, steatotic liver disease, atherosclerosis, and cardiovascular disease. EVs play a critical role in modulating insulin sensitivity, glucose homeostasis, systemic inflammation, and vascular health by transferring functional molecules to target cells. Understanding the EV-mediated network offers potential for identifying novel biomarkers and therapeutic targets, providing opportunities for EV-based interventions in cardiometabolic disease management. Although many challenges remain, this evolving field highlights the need for further research into EV biology and its translational applications in cardiovascular and metabolic health.